Hydrodynamics of Direct Contact Condensation Process in Desuperheater - Hassan A., Ghazwani; Afrasyab, Khan; Pavel Alexanrovich, Taranenko; Vladimir Vladimirovich, Sinitsin; Mofareh H. H., Ghazwani; Ali H., Alnujaie; Khairuddin, Sanaullah; Atta, Ullah; Andrew Ragai, Henry Rigit (MDPI, 2022)
Due to global environmental conditions, the focus of household heating has shifted from fossil fuels towards environmentally friendly and renewable energy sources. Desuperheaters have attracted attention as a domestic provision involving steam-induced direct contact condensation (DCC)to warm the water. The present study is an attempt to investigate the hydrodynamics in the desuperheater vessel experimentally, namely, when the pressurized pulsating steam is injected into the vessel, where the steam jet interacts co-currently with the slow-moving water. Flow visualization showed a circulation region when the pulsating steam was injected into the slow-moving water, and the peaked vorticity corresponded to the steam injection duration of 10–60s.Sevenhot film anemometers (HFAs) were traversed axially and radially to determine the velocity fluctuations at 0–20 cm from the steam’s nozzle exit. Vortical structures indicated the entrainment of the steam with the surrounding moving water. The circulation regions were thus exhibited in relation to the steam’s injection durations as well as the downstream axial distances of 2 and 15 cm from the nozzle exit, which showed that the core local circulation at 2 cm downstream of the nozzle exit lost 75–79% of its circulation at 15 cm downstream of the nozzle exit.